Evaluasi User Experience Pada Game Augmented Reality (Sub Projection Mapping ) : Wall Climbing Menggunakan Heuristic Playbility (PLAY) (Studi Kasus : Wahana Jawa Timur Park 3) - Aryo Seto Dwisaputra; Retno Indah Rokhmawati; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Climbing Wall with Augmented Reality is one of attractions in Funtech, Jawa Timur Park 3. This games combines Projection Mapping techonlogies with conventional climbing wall which has been modified so it can be played for everyone, especially for kids. A new kind of user experience that occur in augmented reality is the reason of this study. Playtesting method used with Heuristic Playbility (Play) as instrument. There are 30 visitors of Funtech who played Climbing Wall as respondent with different background. The result of this study show that there are no different between dimension insisde heuristic playbility instrument with significance rate. The conclusion from those 3 categories are Climbing Wall games has provided a unique and good experience for the player itself. Meanwhile, there are some troubles like control of the game that decrease user experience.